Analysis of surface-state and impact-ionization effects on breakdown characteristics and gate-lag phenomena in narrowly recessed gate GaAs FETs. - Mitani, Y. (IEEE Transactions on electron devices)
Effects of surface states and recess structures on breakdown characteristics of GaAs MESFETs are studied by two-dimensional (2-D) analysis. It is shown that the breakdown voltage could be raised when moderate densities of surface states are included. However, in a case with relatively high densities of surface states, the breakdown voltage could be drastically lowered when introducing a narrowly recessed gate structure. Effects of impact ionization on gate-lag phenomena in GaAs MESFETs are also studied. It is shown that the gate-lag becomes weaker when including the impact ionization. This is attributed to the fact that the potential profiles along the surface are drastically changed when the surface states capture generated carriers. It is suggested that there is a tradeoff relationship between raising the breakdown voltage and reducing the gate-lag.